Design of small heat exchanger (double pipe type) - Mohamad Shafiq, Alias (2010)
Heat exchanger is one of the important devices in cooling and heating process in factories, buildings, transports and others. The heat exchanger is found in large construction to support cooling process such as fossil fuel power plant. For this research, the small heat exchanger of double pipe type is constructed which wants to make it practicality in daily life such for saving fuel in vehicle. So, in this research, the best design for the small double pipe heat exchanger is choose based on TEMA specification. For this research, the hot air from engine bay is cooling down by using water pipe as the cold water where the temperature inlet and outlet for both fluids are specified. In this research, the properties of materials and its size are considered design process. After choosing the best design, the heat exchanger is fabricated by using sawing, flame-cutting, oxy-acetylene welding and drilling. The experiment is performed under two difference conditions where cold water flow rate is manipulated. From the experiment, the temperature of the hot air is dropped faster when using high flow rate of water with constant flow rate of hot air and the overall heat transfer coefficient is increased when water flow rate is increased.